User‐friendly markers linked to Fusarium wilt race 1 resistance Fw gene for marker‐assisted selection in pea. Issue 6 (4th September 2013) - Kwon, Soon Jae; Smýkal, Petr; Hu, Jinguo; Wang, Meinan; Kim, Sung‐Jin; McGee, Rebecca J.; McPhee, Kevin; Coyne, Clarice J.; Link, W.
Abstract Fusarium wilt is one of the most widespread diseases of pea. Resistance to Fusarium wilt race 1 was reported as a single gene, Fw, located on linkage group III. The previously reported AFLP and RAPD markers linked to Fw have limited usage in marker‐assisted selection due to their map distance and linkage phase. Using 80 F8 recombinant inbred lines (RILs) derived from the cross of Green Arrow × PI 179449, we amplified 72 polymorphic markers between resistant and susceptible lines with the target region amplified polymorphism (TRAP) technique. Marker–trait association analysis revealed a significant association. Five candidate markers were identified and three were converted into user‐friendly dominant SCAR markers. Forty‐eight pea cultivars with known resistant or susceptible phenotypes to Fusarium wilt race 1 verified the marker–trait association. These three markers, Fw_Trap_480, Fw_Trap_340 and Fw_Trap_220, are tightly linked to and only 1.2 cM away from the Fw locus and are therefore ideal for marker‐assisted selection. These newly identified markers are useful to assist in the isolation of the Fusarium wilt race 1 resistance gene in pea.